Warehouse Location Determination with GIS within the Scope of Disaster Logistics: Example of Kilis Province - Büşra Kaya Zelzele; Mustafa Ergün (Doğal Afetler ve Çevre Dergisi)
Natural disasters include events that significantly affect human life. Today, the damage caused by natural disasters is increasing due to factors such as climate change and unplanned construction. Turkey is located in a geography where different types of disasters are frequently experienced. These disasters can cause loss of life and property, social and economic damages. Disaster management aims to minimize the damages of disasters, provide rapid intervention and ensure the safety of society. The development of science and technology helps us understand the causes of disasters and develop protection strategies. Geographic Information Systems (GIS) are a powerful tool in reducing disaster damages. Determining logistics warehouse locations by evaluating factors such as risk analysis, infrastructure status, and analysis of transportation networks before disasters plays an active role in disaster management. This study focuses on determining logistics warehouse locations within the scope of disaster logistics using a GIS-based analysis method, and contributes to logistics planning processes for disasters by determining safe logistics warehouse locations with analytical tools and spatial data integration. Within the scope of the study, safe warehouse locations were determined in Kilis province with analyses supported by expert opinions and literature review during the site selection process.